Report on the validation of "Sustainable land use practices: increasing soil fertility, effective use of water resources, and increasing the efficiency of agrotechnical activities" workshop - Akramkhanov, Akmal; Verbist, Joren; Umarova, Shakhzoda (2024)
The present report describes the conducted survey on the 18th of December 2023. The report highlights the purpose of organized workshop, speakers and their presentations, participants' feedback on the content, list of participants, and agenda.